2017
DOI: 10.1183/13993003.00037-2017
|View full text |Cite
|
Sign up to set email alerts
|

The risk of mycobacterial infections associated with inhaled corticosteroid use

Abstract: Inhaled corticosteroid (ICS) use is associated with an increased risk of pneumonia. This study was performed to determine if ICS use is associated with an increased risk of nontuberculous mycobacterial pulmonary disease (NTM-PD) or tuberculosis (TB).We conducted a population-based nested case-control study using linked laboratory and health administrative databases in Ontario, Canada, including adults aged ≥66 years with treated obstructive lung disease ( asthma, chronic obstructive pulmonary disease (COPD) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
116
2
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(137 citation statements)
references
References 44 publications
13
116
2
6
Order By: Relevance
“…This could be because they were seen more frequently by a physician or because there was concern over the known association between ICS and respiratory tract bacterial infections. [26][27][28][29] However, a past history of hospitalised pneumonia was not associated with ICS withdrawal and many resumed ICS use. Encouragingly, and as we have shown before in a different UK primary care patient cohort, 3 patients that were prescribed triple therapy, had more severe disease and were more likely to exacerbate than those prescribed dual therapy.…”
Section: Ics-containing Regimensmentioning
confidence: 99%
“…This could be because they were seen more frequently by a physician or because there was concern over the known association between ICS and respiratory tract bacterial infections. [26][27][28][29] However, a past history of hospitalised pneumonia was not associated with ICS withdrawal and many resumed ICS use. Encouragingly, and as we have shown before in a different UK primary care patient cohort, 3 patients that were prescribed triple therapy, had more severe disease and were more likely to exacerbate than those prescribed dual therapy.…”
Section: Ics-containing Regimensmentioning
confidence: 99%
“…GOLD 2019 recommends LAMA monotherapy as initial treatment in the majority of COPD patients; however, many patients remain symptomatic on monotherapy, and LABA/LAMA is recommended in these patients . On the other hand, use of ICS in COPD is associated with side effects—pneumonia, diabetes, osteoporosis and mycobacterial infections . Furthermore, as per GOLD 2019 update, initial treatment with LABA/ICS may be the first choice only for COPD patients with history of asthma or with blood eosinophil counts ≥300 cells/μL .…”
Section: Discussionmentioning
confidence: 99%
“…2,35,36 On the other hand, use of ICS in COPD is associated with side effects-pneumonia, diabetes, osteoporosis and mycobacterial infections. [37][38][39][40] Furthermore, as per GOLD 2019 update, initial treatment with LABA/ICS may be the first choice only for COPD patients with history of asthma or with blood eosinophil counts ≥300 cells/μL. 2 LABA/LAMA combinations, particularly IND/GLY, have shown improvements in lung function, PRO, rescue medication use and exacerbations versus monocomponents, placebo and well-established COPD treatments including LAB-A/ICS.…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk of NTMLD in COPD subjects may be partly associated with inhaled steroids use and dosage [26,27]. Diel et al [28] found an increased mortality rate among COPD individuals infected with NTM, comparing to those not infected.…”
Section: Discussionmentioning
confidence: 99%